Alexander von Humboldt, writer and reader of Hispanic travels: Postcolonial Eurocentrism or intertextual alterity? - Del Pino-Díaz, Fermín (2022)
Starting from a vital review of A. de Humboldt’s journey to the New World, his work as a reader of chronicles of the Indies is particularly examined, a well-connected part of his editorial work as a scientific traveler. All of this serves to reflect on the intertextual debt of travel chronicles and, above all, on Humboldt’s particularly honest and generous relationship with the Spanish- American republic of letters and with its plural civilization. All this leads the author to question some accepted paradigms within the intellectual field called postcolonialism.